Analisis Yuridis Keabsahan Perjanjian Pinjaman Online Spinjam Pada Aplikasi Shopee Berdasarkan Kitab Undang-Undang Hukum Perdata : Juridical Analysis Of The Validity Of Online Loan Agreements Spend On The Shopee Applicatio Based On The Book Civil Law Act - Vivi Humaera (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2023)
In this research the author raised the title "Judicial Analysis of the Validity of Online Loan Agreement on the Shopee Application". The purpose of this research is to find out the problems that will be examined in this thesis are: How is the validity of online loan agreements based on the provisions of the Civil Code and what is the legal protection for debtors and creditors when using online loan agreement on the Financial Technology-based Shopee application. The research method used is normative-empirical law and the specifics used in this research are descriptive analysis. Based on research results, legally, fintech agreements remain valid if they meet subjective and objective requirements. On the other hand, the fintech agreement is made by the organizer, not made by the parties as users. in fintech agreements. If the agreement fulfills these elements, then the fintech agreement is valid according to law. Legal protection for parties in the implementation of online-based money lending and borrowing includes preventive and repressive legal protection, where preventive law is based on its implementation before a dispute occurs. Meanwhile, repressive legal protection is carried out after a dispute occurs.